Measurement of metallic contaminants in food with a high-Tc SQUID - Tanaka, Saburo; Hatsukade, Yoshimi; Aspanut, Zarina; Matsuda, Takemasa; Hotta, Naoki; Uchida, M.; Natsume, Miyuki (2004)
We have proposed and demonstrated a high-Tc SQUID system for detecting metallic contaminants in foodstuffs. There is a demand for the development of systems for detecting not only magnetic materials but also non-magnetic materials such as Cu and aluminium in foodstuffs to ensure food safety. The system consists of a SQUID magnetometer, an excitation coil and a permanent magnet. For a non-magnetic sample, an AC magnetic ﬁeld is applied during detection to induce an eddy current in the sample. For a magnetizable sample, a strong magnetic ﬁeld is applied to the sample prior to the detection attempt. We were able to detect a stainless steel ball with a diameter of 0.1 mm and a Cu ball less than 1 mm in diameter, for example.